DEVELOPMENT STRATEGY FOR TIDAL SWAMP AGRICULTURAL AREAS IN ECONOMIC DEVELOPMENT IN BANYUASIN REGENCY, SOUTH SUMATRA PROVINCE - Sukardi Sukardi; Fachrurrozie Sjarkowi; Elisa Wildayana; Desi Aryania (Jurnal Ekonomi, 2023)
Technological innovation in agriculture is essential not only to enhance productivity and ensure food availability but also to preserve the environment. Several basic principles of sustainable agricultural development include community-based initiatives, environmental conservation, involvement of agribusiness actors, focus on the development of small-scale farming, and reliance on local resources. The utilization of tidal swamp land in Banyuasin Regency covers an area of 163,758 hectares, consisting of 16 tidal swamp irrigation regions under the authority of the central government. Through the implementation of the SERASI program from 2019 to 2021, it has been proven to reduce poverty rates in Banyuasin Regency. The objective of this research is to formulate the policy direction for the development of tidal swamp agriculture that supports economic development in Banyuasin Regency. The research aims to formulate the policy direction for the development of tidal swamp agriculture that supports economic development in Banyuasin Regency. The research findings indicate the following: enhancing the practice of agricultural intensification in tidal swamp land through increased farmer knowledge and expanding funding opportunities for the application of agricultural technology; expanding the adoption of sustainable farming practices through technology implementation, particularly in soil processing, water management, fertilizer selection, pest and disease control, harvesting, and post-harvest handling, which can prevent and minimize the risk of land degradation; preserving the sustainability of tidal swamp agricultural land through effective irrigation system management by activating irrigation management institutions, especially at the farmer level, and implementing soil management practices to maintain soil fertility; improving the welfare of farmers through demographic and social improvements, such as increasing farmer education, promoting a greater number of creative and innovative young farmers, strengthening farmer groups/institutions, fostering partnerships, and involving all members of farmer families.